Productivity and accumulation of heavy metals in grain of various genotypes of spring durum wheat under conditions of soil contamination with cadmium and zinc (Eurasian Journal of Ecology, 2021)
The developed industry has an adverse effect on the ecological state of the environment, accompanied by the accumulation of harmful substances in the soil, including heavy metals. Therefore, thecreation of technogenically resistant varieties of agricultural crops is one of the components of environmentally friendly technologies. This study is aimed at studying various genotypes of spring durum wheatfor their resistance to the accumulation of cadmium and zinc in grain, which is a commercial part ofthe product. The content of the studied heavy metals in the soil of the root zone of various genotypesof spring durum wheat was investigated. The accumulation of the studied elements in seeds was determined, which is the most important studied indicator. The indices of productivity and survival of springdurum wheat genotypes were investigated in the field of natural pollution of the environment with heavymetals. The most stable and sensitive to the action of cadmium and zinc genotypes were revealed. Thestructure of spring wheat productivity from the collection and the relationship of its elements wereanalyzed. The identified resistant genotypes are recommended for further study of their productivityand survival in weather conditions of the East Kazakhstan region in field experiments to identify formspromising for agricultural production.Key words: cadmium, zinc, spring durum wheat.